2019
DOI: 10.1111/jiec.12964
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle sustainability assessment of autonomous heavy‐duty trucks

Abstract: Connected and automated vehicles (CAVs) are emerging technologies expected to bring important environmental, social, and economic improvements in transportation systems. Given their implications in terms of air quality and sustainable and safer movement of goods, heavy-duty trucks (HDTs), carrying the majority of U.S. freight, are considered an ideal domain for the application of CAV technology. An input-output (IO) model is developed based on the Eora database-a detailed IO database that consists of national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…In addition, environmental benefits could be paid back in less than five years if freight traffic volumes were sufficiently high. Sen et al [63] assessed the impact of automated diesel and battery electric heavyduty trucks in terms of environmental, economic, and social aspects with 20 macro-level indicators. The resulting analysis suggested that policymakers should drive people to consider alternative energy sources to reduce GHG emissions generated by electricity generation in the United States for batteries.…”
Section: Recent Technological Developments In Battery-electric Heavy-duty Vehiclesmentioning
confidence: 99%
“…In addition, environmental benefits could be paid back in less than five years if freight traffic volumes were sufficiently high. Sen et al [63] assessed the impact of automated diesel and battery electric heavyduty trucks in terms of environmental, economic, and social aspects with 20 macro-level indicators. The resulting analysis suggested that policymakers should drive people to consider alternative energy sources to reduce GHG emissions generated by electricity generation in the United States for batteries.…”
Section: Recent Technological Developments In Battery-electric Heavy-duty Vehiclesmentioning
confidence: 99%
“…In [19], Enhanced Convolution neural network with Support Vector Machine (ECNN-SVM) based vehicle detection was proposed for efficient computation. In [20], a life cycle sustainability assessment was proposed for ensuring smooth tracking in self-driven heavy-duty trucks.…”
Section: Related Workmentioning
confidence: 99%
“…The life cycle assessment (LCA) has been widely utilized to assess the environmental footprints across the EV's life cycle phases, including material extraction, manufacturing, usage, and end-of-life (Sen, Kucukvar, Onat, & Tatari, 2020;Sen, Onat, Kucukvar, & Tatari, 2019;Onat et al 2014Onat et al a,b, 2019. Usai et al (2021) conducted an LCA on fuel cell systems for fuel cell electric vehicle (FCEVs) technologies to understand the environmental impacts associated with the use of FCEVs in the United States.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%